Autoimmune Hepatitis: 2019 Update - Tanaka, Atsushi (Gut Liver, 2020)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease, characterized by the elevation of aminotransferases, presence of anti-nuclear antibody or anti-smooth muscle antibody, elevated immunoglobulin G (IgG), and interface hepatitis/plasma-lymphocytic inflammation based on histology. Recent epidemiological studies have indicated an increasing trend in the prevalence of AIH worldwide, especially in male patients; this trend may suggest the alteration of environmental triggers of disease onset over time. As no disease-specific biomarker or histological finding is currently available, AIH requires a clinical diagnosis, and a validated diagnostic scoring system with acceptable specificity and sensitivity has been proposed. Regarding treatment, corticosteroids and azathioprine are recommended, and in those who exhibit an incomplete response or those who are intolerant to these drugs, second-line therapy, such as mycophenolate mofetil, is considered. Overall, the long-term outcome is excellent in patients with complete biochemical responses, while life-long maintenance treatment may be required since the cessation of immunosuppressive agents frequently leads to the relapse of the disease. Acute-onset AIH does occur, and the diagnosis is very challenging due to the lack of serum autoantibodies or elevated IgG. The unmet needs include earlier diagnosis, intervention with disseminated clinical practice guidelines, and recognition and improvement of patients’ health-related quality of life with the development of novel corticosteroid-free treatment regimens.